Synovial sarcoma of submandibular gland with aberrant P63 expression a case report of rare event - Afnan Elsayed; Haneen Al-Maghrabi; Hosam Alardati; Ameen Alherabi; Abdelrazak Meliti (Elsevier, 2019)
Synovial sarcoma is a tumor commonly involves extremities and periarticular soft tissue of young adults. Head and neck region is involved in 10% of cases, mostly biphasic in histology. Submandibular gland is an uncommon anatomic location for primary synovial sarcoma. Herein, we present a unique case of primary submandibular gland synovial sarcoma morphologically mimicking a solitary fibrous tumor. Moreover, the neoplastic cells reveal an aberrant p63 nuclear expression. The immunoprofile and the molecular studies confirmed TLE1 expression and SYT (18-11.2) rearrangement, respectively. To the best of our knowledge, the present case is the first with a p63 expression and the second reported case of primary submandibular gland synovial sarcoma in English literature. Keywords: Synovial sarcoma, submandibular gland, aberrant p63 expression